Assessment of Zinc Deficiency and Nutritional Status among Pregnant Women from District Mardan, KP Pakistan - Noor, Sara; Faqir, Shujaat; Ijaz, Fatima; Sattar, Irfan; Bibi, Ayesha; Ali, Fawad (Indus Journal of Bioscience Research, 2025)
Pregnancy-related zinc deficiency (ZD) has detrimental consequences on both the mother and the fetus, as well as subsequent implications on birth. It is estimated that 82% of all pregnant women in the world suffers from zinc deficiency. Lack of information on the zinc status of the population has significantly limited the adoption of strategies to control zinc. Assessment of the overall nutritional status, dietary intake and prevalence of zinc deficiency of pregnant women in District Mardan was measured. The study included 200 pregnant women from various hospitals of District Mardan. A pre-planned questionnaire was used to gather information. Statistical Package for Social Sciences (SPSS) was used to analyze the data. The mean age of the subjects was 35 years. Majority (65.5%) and (63%) had low hemoglobin and zinc level. Majority of the subjects were experiencing hair loss, changes in nails, diarrhea, nausea and vomiting. Exercise of daily basis was recorded for only (6.5%) of the subjects. Most (52.5%) of the subjects were having 1 to 3 hours of sleep. Zinc rich foods like Oat, egg yolk, kidney bean, Peanut, yogurt and chicken were consumed by majority of respondents. Food dense in macro and micronutrients should be consumed by respondents. Nutritional interventions should target pregnant women to improve maternal nutritional status to overcome maternal and fetus health issues.